Discerning the crystal structure and engineering the optoelectronic properties through substitution of divalent cations (M= Zn, N = Ge) in C3H3MxN1-xI3 for solar cell applications. (15th June 2023) - Kruthika, G.; Ravindran, P.
Abstract: Herein, we identified the ground state crystal structures of C3 H3 Zn x Ge 1-x I3 hybrid perovskite materials and investigated their optoelectronic properties for the first time using van der Waals correction, included ab initio calculations with hybrid functionals. The energy difference and formation energy calculations are done to perceive the information related to their structural phase transition and stability. Chemical bonding between the atomic constituents are found from charge density distribution, projected crystal orbital Hamiltonian population (pCOHP) and its integration (IpCOHP) results. Our electronic structure calculations predict the compositions with x = 0, 0.25, 0.5, 0.833 as indirect band gap materials and x = 0.667 and 1 as direct band gap materials. Our results also predict that the composition with x = 0.833 value belongs to the classification of intermediate band gap semiconductor. The effective mass of holes and electrons are calculated at valence and conduction band edges, respectively, to realize the transport property of carriers. The absorption coefficient calculations infer that composition with x = 0.667 shows better optical absorption property in the visible region compared to other compositions. The applicability of these materials towards solar cell device performance is explored by calculations of cell parameters and it is found that the power conversion efficiency is higher for the composition with higher Ge concentration than Zn. Specifically, low PCE values in the range of 8.66–17.32% corresponds to C3 H3 Zn0.833 Ge0.167 I3 and high PCE values in the range of 16.52–33.04% corresponds to C3 H3 Zn0.5 Ge0.5 I3 . Graphical abstract: The ground state crystal structure of C3 H3 M x N 1-x I3 ( M = Zn, N = Ge) is orthorhombic and monoclinic when x is 0 and 1, respectively. It is found that orthorhombic crystal structure is preferred for x = 0, 0.25, 0.5 and a phase transition occurs at x = 0.56 and then monoclinic crystal structure is preferred for x = 0.667, 0.833, 1. Increase in Zn concentration improves the optoelectronic properties of the materials. Image 1 Highlights: Prediction of crystal structures of C3 H3 M x N 1-x I3 ( M = Zn, N = Ge) through ab - initio calculations. The increase in Zn concentration in C3 H3 M x N 1-x I3 improves their phase stability and optoelectronic properties. Solar cell parameters calculation states that the Ge possessing compounds are superior to their Zn counterparts.